2012
DOI: 10.1158/1078-0432.ccr-11-3369
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of Ganitumab (AMG 479) Combined with Sorafenib, Panitumumab, Erlotinib, or Gemcitabine in Patients with Advanced Solid Tumors

Abstract: Purpose: This phase 1b dose-escalation study assessed safety, tolerability, and pharmacokinetics of ganitumab, a fully human monoclonal antibody against the insulin-like growth factor 1 (IGF1) receptor, combined with targeted agents or cytotoxic chemotherapy in patients with advanced solid tumors.Experimental Design: Patients with treatment-refractory advanced solid tumors were sequentially enrolled at 2 ganitumab dose levels (6 or 12 mg/kg i.v. every 2 weeks) combined with either sorafenib 400 mg twice daily,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The IGF-IR and ErbB3 signaling pathways have been implicated as potential escape pathways in cancers exhibiting resistance to targeted therapies and chemotherapies (18)(19)(20)(21)(41)(42)(43)(44)(45). We demonstrate that the IGF-IR pathway is often coactivated with ErbB3, another nonoverexpressed receptor.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The IGF-IR and ErbB3 signaling pathways have been implicated as potential escape pathways in cancers exhibiting resistance to targeted therapies and chemotherapies (18)(19)(20)(21)(41)(42)(43)(44)(45). We demonstrate that the IGF-IR pathway is often coactivated with ErbB3, another nonoverexpressed receptor.…”
Section: Discussionmentioning
confidence: 74%
“…We have previously shown that direct targeting of ErbB3 is optimal for blocking the ErbB3-PI3K cascade (32). Recent clinical strategies have combined IGF-IR inhibitors with EGFR-based therapies resulting in disappointing outcomes (19)(20)(21). We propose that the simultaneous blockade of IGF-IR and ErbB3 is necessary to maximize the potency of PI3K/ AKT/mTOR inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase Ib study assessed the impact of ganitumab in advanced solid tumors including one patient with advanced PCa. The patient treated with the combination ganitumab 12 mg/m 2 + gemcitabine tolerated the drug without side effects [67]. Subsequently, another Phase I study was initiated including a higher number of patients with advanced PCa (NCT00562380).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…In human pancreatic cancer xenograft models, the combination of ganitumab with gemcitabine demonstrated inhibition of cell growth and proliferation [25]. In a Phase Ib study, this combination was associated with a disease control rate (complete response plus partial response plus stable disease) of 80% in patients with advanced solid tumors including pancreatic cancer [26]. A randomized Phase II study in untreated metastatic PDAC demonstrated tolerable toxicity with a trend toward improved OS [27].…”
Section: Ganitumab (Amg 479)mentioning
confidence: 99%